Early detection of prostate cancer using extracellular vesicles and nanoparticle-aided time-resolved fluorescence immunoassay - Rahman, Mafiur (My University, 2023)
Prostate cancer (PCa) is a type of cancer that affects the prostate, an organ in the male reproductive system. It is mostly diagnosed and deadliest cancers among men. In 2020, approximately 1.4 million new cases were diagnosed, causing 370,000 deaths. Although there are available biomarker-based techniques for detecting PCa, for example Prostate Specific Antigen (PSA), but they have a set of drawbacks. Therefore, extracellular vesicles (EVs) could be an option to solve this problem. In this study, we investigated whether utilizing a high-throughput method (FastEVTM) for enriching EVs from clinical serum samples, in combination with nanoparticle-aided time-resolved fluorescence immunoassay (TRFIA) could enhance the accessibility of biomarkers for the early detection of PCa. EVs- and soluble protein (SP)-fractions were separated from both PCa and benign prostate hyperplasia (BPH) patients using the FastEV technology. Biotinylated capture antibody was immobilized on streptavidin coated microtiter wells for capturing EV and SP-fractions of PCa. Then captured analyte was detected using glycan- binding lectin coated on nanoparticles (NPs). We have observed that assay consisting with cancer antigen (Ca15.3) and (Ca19.9) in combination with WGA lectin, such as Ca15.3WGA and Ca19.9WGA assays were able to significantly separate the PCa patients from the BPH sources (p-value = 0.007 and 0.00001), respectively. In this study we have demonstrated that high-throughput method (FastEVTM) along with simple nanoparticle-aided time-resolved fluorescence immunoassay (TRFIA) could be used to detect PCa patients from clinically challenged BPH conditions.
Keywords: prostate cancer, prostate specific antigen, extracellular vesicles, immunoassay, microtiter, capture, lectin.